Integration of entrepreneurship into higher education as a premise for youth well-being in Lithuania and Latvia - Melnikova, Julija; Ahrens, Andreas; Zaščerinska, Jeļena (Social Welfare: Interdisciplinary Approach, 2017)
The purpose of this article is to highlight the aspects of integration of entrepreneurship into higher education in Lithuania and Latvia. The promotion of youth entrepreneurship as a means of improving youth well-being in these countries has recently attracted increasing attention from scholars and policy makers. The integration of entrepreneurship into higher education is one of strategic pathways in the improvement of the quality of higher education and the promotion of youth effective participation in labour market. It is argued in the article that integration of entrepreneurship into higher education is supposed to be the factor of the development of Lithuania and Latvia’s socio-economic situation. Models of youth’s entrepreneurial competencies are highlighted theoretically and some empirical insights on which competencies students from Lithuanian and Latvian universities would like to have acquired are provided.
Keywords: entrepreneurship; higher education; youth; well-being